Métodos de punto interior para optimización cuadrática convexa con matrices no definidas positivas - Palencia F., Gonzalo (2008)
In this article a modification of the recursive algorithm of Cholesky is obtained that allows the factorization of Semi Definite Positive Matrices, even though these are not positive defined, without increasing the computational cost. Thanks to this factorization Convex Quadratic Programming Problems are transformed into Second Order Conical Problems, which are solved with the aid of the generalization of the Predictor-Corrector algorithm of Mehrotra for these problems. There are carried out numeric experiments for validating the results.